Caracterização de fatores regulatórios determinantes dos efeitos alélicos do gene de tolerância ao alumínio SbMATE em sorgo - Janaina de Oliveira Melo (2012)
Aluminum (Al) toxicity is one of the major factors limiting crop yield on acid soils. Al tolerance in sorghum is conferred by the AltSB locus, which is located on chromosome 3. Within AltSB, SbMATE encodes an Al-activated citrate transporter that underlies Al tolerance. Polymorphisms were previously found in the promoter and within introns, suggesting that causative mutations associated with Al tolerance are mainly regulatory in nature. Thus, the aim of the present study was to characterize the mode of action of regulatory effects, whether acting in cis and/or trans to modulate the expression of sorghum SbMATE. Near isogenic lines (NILs) were generated by introgressing the AltSB locus from donors showing different levels of Al tolerance into the background of BR012, an Al sensitive line. A reduction in both Al tolerance and SbMATE expression was observed in the NILs when compared with the respective parental lines, indicating the importance of trans-acting factors. In addition, the extensive allelic variability observed in NILs for Al tolerance indicated a role also for cisacting factors. This work has also uncovered the occurrence of alternative splicing of SbMATE. The different isoforms were induced by Al treatment with expression increasing as the time of exposure to the metal progressed, particularly in tolerant lines. The SbMATE sequence of different sorghum lines was characterized and the coding region was in general identical between lines. However, a single SNP was identified in the first exon of SC566, a highly tolerant line. Hybrids between SC566 and lines differing to their degree of Al tolerance and SbMATE expression were generated. In addition, a NIL harboring the SC566 allele was crossed to other NILs on the same background. Extensive plasticity in mode of gene action was observed from the global expression analysis of both SbMATE alleles in the hybrids, including the detection of overdominance. The SNP identified in SC566 was used to develop an allele-specific expression assay in order to analyze, simultaneously, the expression of each SbMATE allele in hybrid stocks. The expression of the allele coming from the Al sensitive parent was induced in the hybrids, complementing the low level of expression present in the Al sensitive parents. However, a reduction in expression of the Al sensitive allele was observed in hybrid stocks between the SC566-NIL and other NILs. In these stocks, only the AltSB locus was heterozygous with the rest of the genome belonging to the Al sensitive line, BR012. These results suggest that SC566 harbors trans-acting factors located out of the AltSB locus, which can complement the low expression phenotype observed in alleles derived from Al sensitive lines. The results are also compatible with overdominance being caused by induction in expression of the Al sensitive alleles caused by trans-acting factors donated by SC566. The results generated here will contribute to the formulation of advanced strategies of molecular breeding of Al tolerance in sorghum.